Uneven plastic deformation behavior of high-strength cast aluminum alloy tube in multi-pass hot power backward spinning. Issue 1 (January 2017) - Zhao, Gangyao; Lu, Chengjun; Zhang, Ranyang; Guo, Zhenghua; Zhang, Mingyuan
Abstract Uneven plastic deformation plays an important role in the multi-pass hot power backward spinning of high-strength cast aluminum alloy tube, which can lead to defects produced such as crack, bulge, and bell mouth if it is controlled improperly. To predict and control the uneven plastic deformation, a 3D coupled thermo-mechanical FE model of the process was built under the ABAQUS/Explicit environment. And several key techniques, such as loading trajectory, heat boundary condition treating, and material properties definition, are solved. Then the uneven deformation behavior in the process was analyzed systematically. The results show the following: (1) The variations of stress, strain, and temperature are produced, firstly, in the spinning zone and then move toward the tube bottom with the roller during spinning process. (2) In the spun zone, the temperatures of inner and outer surfaces of the tube are similar, while in the ring zone contacted with the roller, the temperature decreases gradually from the inner surface of the tube to the outer surface. And a higher temperature zone with a ring-shaped is produced gradually in the contact zone between the tube and roller. (3) The maximum equivalent strain increases with the process of the tube spinning while fluctuation is produced in the maximum equivalent stress. The equivalent strain of inner surface of the tube is larger than that of the outer surface in the spun zone. And the maximum temperature is produced in the early spinning stage of the each pass. (4) In the spun zone, the axial, tangential stresses and axial, normal strains are much larger than normal stress and circumferential strain, respectively. And triaxial states of stress and strain exist in the spinning zone of the tube.